ChemInform Abstract: Chemical Synthesis of Homogeneous Glycoproteins for the Study of Glycoprotein Quality Control System. Issue 24 (June 2015) - Izumi, Masayuki; Dedola, Simone; Ito, Yukishige; Kajihara, Yasuhiro
Abstract: Review: [36 refs.